The Impacts of Total Quality Management, Human Resource Management, and Agility in Business on Firms Financial Performance: Moderating Role of Emerging Business Competition - Muhammad Sadiq; Amna Alamgir; Syed Wajahat Ali (iRASD Journal of Management)
The current study explores the nexus of total quality management, human resource management, Agility in business, and firms’ financial performance. The current study's objective also investigates the moderating impact of emerging business competition among the nexus of total quality management, human resource management, Agility in business, and the firm's financial performance. The primary data has been gathered by using questionnaires from Chinese organizations' employees, while smart-PLS has been executed for analysis. The results exposed that total quality management, human resource management, and Agility in business positively associate with firms’ financial performance. The output also shows that the emerging business competition moderated among the nexus of total quality management, human resource management, and firms’ financial performance. These outcomes are suitable for the regulation-making authorities who want to develop quality and human management policies that could increase the firm performance.